Model Kepuasan dan Loyalitas Konsumen: Analisis Brand image, Value, Quality, dan Promotion pada Produk ABC - Wahyudi, Triyono Arief (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2022)
This research aims to see the effect of brand image, perceived value, perceived quality, and perceived promotion to customer satisfaction and its impact on customer loyalty produk abc. this research was conducted by quantitative research method with survey method on sample of building material store, gypsum store, applicator contractor in jabodetabek. samples were taken by purposive sampling method in which 180 samples were chosen based on predetermined criteria. the result of the research is (1) brand image has a positive and significant influence on customer satisfaction, (2) perceived value has a positive and significant influence on customer satisfaction, (3) perceived quality has a positive and significant influence on customer satisfaction, (4) perceived promotion has a positive and significant influence on customer satisfaction, (5) customer satisfaction a has positive and significant influence on customer loyalty.